The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.esxm.2020.100311
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Psychological Evaluation for Patients Referred for Penile Prosthesis Implantation

Abstract: Background: Patients may remain dissatisfied after penile prosthesis implantation for the treatment of erectile dysfunction. Studies showing the results of standardized protocols for preoperative psychological evaluation are lacking. Purpose: To estimate the rate of patients considered psychologically unfit for penile prosthesis implantation and to compare their characteristics with those considered fit after the implementation of a standardized psychological profile evaluation protocol for men with erectile d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…In addition to directly querying psychiatric history, a review of current medications may indicate ongoing treatment for psychiatric conditions. A history of psychiatric comorbidities may suggest increased risk for dissatisfaction, but the more important aspect of this initial assessment is to determine if a patient has active, untreated symptoms that may require additional support ( 11 ). Patients with poorly managed psychiatric conditions may not have the psychological reserve or ability to cope with a significant complication.…”
Section: Preoperative Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to directly querying psychiatric history, a review of current medications may indicate ongoing treatment for psychiatric conditions. A history of psychiatric comorbidities may suggest increased risk for dissatisfaction, but the more important aspect of this initial assessment is to determine if a patient has active, untreated symptoms that may require additional support ( 11 ). Patients with poorly managed psychiatric conditions may not have the psychological reserve or ability to cope with a significant complication.…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…Previous studies have demonstrated that the incidence of anxiety or depressive symptoms is 13.8–17.1% in men with ED ( 11 ). Failure to recognize psychiatric comorbidities may lead to surgical complications, prolonged hospital stay, readmission, and overall decreased patient satisfaction ( 12 - 15 ).…”
Section: Introductionmentioning
confidence: 99%